Canadian International Petroleum Conference 2000
DOI: 10.2118/2000-012
|View full text |Cite
|
Sign up to set email alerts
|

Improved Estimation of Gas Well Deliverability from Single-Point Tests

Abstract: Chase and Alkandari developed dimensionless inflow performance (IPR) curves for predicting the stabilized deliverability of hydraulically fractured gas wells using just a single-point test, namely a pressure build-up or draw-down test. Unfractured wells can also be analyzed by converting the apparent skin factor to an equivalent ratio of X e /X f . Results obtained from the dimensionless IPR curve model can be used to generate values of n and C for the equation of stabilized deliverability. This research descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Note that Chase et al 9,10 showed that using the dimensionless IPR method produced more accurate deliverability forecasts than those obtained by simply using equation (1) with the assumption that the exponent, n, was equal to one.…”
Section: Discussion Of Simulated Well Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that Chase et al 9,10 showed that using the dimensionless IPR method produced more accurate deliverability forecasts than those obtained by simply using equation (1) with the assumption that the exponent, n, was equal to one.…”
Section: Discussion Of Simulated Well Resultsmentioning
confidence: 99%
“…Using Joshi's Equation given by: ………………. (9) where, …………….. (10) and Russell and Truitt's Equation given by: r w´ = 0.37 X f ..……………………..……………..………. (11) the following new relationship was derived:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation